Realizing Justice and Maṣlaḥah in E-Commerce: Fiqh Muamalah Insights and Challenges in Malaysia and Indonesia - Batubara, Chuzaimah; Rokan, Mustapa Khamal; Manaf, Muhammad Firdaus Bin Abdul; Sukiati, Sukiati; Harahap, Isnaini (JURIS (Jurnal Ilmiah Syariah), 2024)
This study explores how fiqh muamalah principles can realise justice and maṣlaḥah in e-commerce practices, focusing on the understanding and behavior of consumers and producers in Malaysia and Indonesia. The research investigates how these Islamic legal principles are integrated and practised within the digital marketplace. The primary data sources include e-commerce users from Malaysia and Indonesia, specifically consumers and producers. Data were collected through in-depth interviews with various e-commerce users, including consumers and producers. The results reveal that producers generally have a higher awareness of justice and ma maṣlaḥah in e-commerce, though their application of these principles varies. Consumers' experiences are inconsistent, often influenced by their educational background and exposure to Islamic commerce teachings. Key challenges include the lack of standardized guidelines and divergent interpretations of fiqh muamalah principles. The study underscores the need for more structured education and regulatory frameworks to ensure these principles' effective and consistent integration into e-commerce practices. Recommendations include developing comprehensive training programs and establishing clear guidelines to bridge the gap between understanding and practice, thereby aligning e-commerce practices in Malaysia and Indonesia with fiqh muamalah principles.